Exploration of operating conditions on oxygen mass transport resistance and performance of PEM fuel cells: Effects of inlet gas humidification. Issue 1 (19th November 2021) - Reshetenko, Tatyana V.; Ben, Bonnie L.
Abstract: This work presents comprehensive studies of inlet gas humidification on O2 mass transport and proton exchange membrane fuel cell performance to obtain a better understanding of transport processes at a cathode gas diffusion electrode. The O2 mass transport resistance was determined employing our segmented cell system and a novel method based on the distribution of the spatial limiting currents using 5% vol. O2 mixtures with various balance gases from He to C3 H8 . Variation of the molecular weight of the balance gas resulted in the determination of O2 mass transport resistance due to Knudsen diffusion as well as diffusion and dissolution through liquid and ionomer films in a cathode catalyst layer ( RK+film ) and gas phase ( Rm, N2 ). The application of a gas diffusion layer with and without a microporous layer (MPL) allowed us to separate contributions from the cathode catalyst layer ( RK+film, CCL ) and MPL ( RMPL ). The data demonstrated that R K+film, CC L significantly decreased from 92.36 to 52.83 s/m at 32 and 100% relative humidity, respectively, due to the effect of humidification on gas permeability through the ionomer. At the same time, Rm, N2 decreased slightly with gas humidification, while RMPL increased slightly. The results showed that fuel cell performance improved with a decrease in permeability mass transport overpotentials and RK+film, CCL . An analysis of the data demonstrated correlations between operating conditions, the mass transport parameters of the cathode gas diffusion electrodes, fuel cell performance, and voltage losses.